Analisis keterampilan menulis karangan deskripsi pada peserta didik kelas iv sekolah dasar - Eni Sundari; Rukayah Rukayah; Dwi Yuniasih Saputri (Didaktika Dwija Indria, 2022)
The purpose of this study was to describe students' descriptive essay writing skills. This type of research is qualitative research and was conducted on fourth grade students of SDIT Islamy. The subject selection technique used purposive sampling and took 20% of the class IV population. Data collection techniques using tests, observations, interviews. Aspects of descriptive essay writing skills are the involvement of the five senses, the suitability of the content with the title, organization, effective sentence mastery and vocabulary selection, and spelling. The results showed that the percentage of sensory involvement aspect was 0%, content conformity with title was 83%, organization was 0%, sentence mastery and effective vocabulary selection was 0%, spelling was 0%. The biggest percentage result is from the aspect of conformity of the content to the title, while the lowest aspect is from the involvement of the five senses, organization, effective sentence mastery and vocabulary selection, and spelling. Based on the previous explanation, it was concluded that the analysis of the descriptive essay writing skills of the fourth grade students of SDIT Islamy was in the very poor category. The theoretical implication of this research is to increase knowledge about the analysis of descriptive essay writing skills.